PERANCANGAN IDENTITAS MEREK DAN KONTEN PEMASARAN LA ORLIND UNTUK MENINGKATKAN BRAND AWARENESS PRODUK KEBAYA UNTUK USIA 18-25 TAHUN DI KOTA MALANG - Kurniawan, Desie; Nirwana, Aditya; Prasetya, Bintang Pramudya Putra (Ma Chung Press, Universitas Ma Chung, 2024)
Fashion plays a crucial role in human life, fulfilling various needs. Despite the continuous evolution of modern fashion trends, traditional attire like the kebaya remains popular. With modern and stylish touches, the kebaya presents an attractive business opportunity, especially in Malang City, where the brand La Orlind capitalizes on this potential. The design of La Orlind's brand identity aims to increase public awareness of the brand, using the Moser method to shape the brand’s identity through core brand values, core brand messages, and brand personality. The outcome of this design process includes La Orlind's logo and a GSM book that contains elements such as the logo, color palette, supergraphics, typography, visual elements, and other supporting media. This design is expected to contribute to the field of brand identity by enhancing brand awareness for the brand.